Transformation of the Forest Sector of Ukraine in the Conditions of Post-War Green Restructuring: Regional Dimension of Public-Private Partnership - Biriushov, Dmitry (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The study examines the transformation of Ukraine’s forestry sector in the context of post-war green reconstruction. The necessity of implementing public-private partnership mechanisms as an instrument of public policy in the field of forest resource management is substantiated. The role of the regional level in the restoration of damaged territories, development of the processing industry, and attraction of investments is determined. The main directions for implementing “green” public-private partnership projects are outlined, including forest land restoration, bioenergy development, and the introduction of digital monitoring systems. It is concluded that combining the resources of the state, territorial communities, and the private sector is essential for ensuring the sustainable development of Ukraine’s forestry sector.